Suran's Re-Existence for Intergenerational Eco-Efforts in Kahuripan Hamlet - Wisnu Sapto Nugroho; Izhak Y.M Lattu; Tony Tampake; Spyridon Tsitsigkos (LPPM Universitas PGRI Sumatera Barat, 2024)
This article aims to explore the existence of Suran in the appreciation of the people of Kahuripan hamlet, Kalirejo village, Bagelen District, Purworejo Regency, Central Java for the realization of intergenerational ecology (intergenerational eco). The research approach used is a qualitative approach with narrative-descriptive data analysis techniques. Data were collected through interviews and literature studies. Research sources came from intergenerational Kahuripan villagers who knew and experienced the Suran tradition. The theory used as an analytical knife is Anthony Giddens' structuration theory and generation theory. This study found that three layers of generations do not know the background of abstinence and Suran rituals, but they believe that Suran is an ancestral heritage that must be preserved. People consider the month of Sura as a sacred month. The sacredness of Sura makes people do